2013
DOI: 10.1158/1078-0432.ccr-13-0674
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Hypoxia-Activated Prodrug, TH-302, in Preclinical Human Acute Myeloid Leukemia Models

Abstract: Purpose: Acute myeloid leukemia (AML) is an aggressive hematologic neoplasm. Recent evidence has shown the bone marrow microenvironment in patients with AML to be intrinsically hypoxic. Adaptive cellular responses by leukemia cells to survive under low oxygenation also confer chemoresistance. We therefore asked whether therapeutic exploitation of marrow hypoxia via the hypoxia-activated nitrogen mustard prodrug, TH-302, could effectively inhibit AML growth.Experimental Design: We assessed the effects of hypoxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 40 publications
2
47
0
Order By: Relevance
“…Antitumor activity of the hypoxiaactivated pro-drug (TH-302) was demonstrated in combination with bortezomib which improved survival of mice with myeloma (14). TH-302 also delayed onset and progression of acute myeloid leukemia (AML) xenograft model (23). Moreover, blocking HIF1a signaling, which is constitutively expressed in mouse lymphoma and human AML stem cells, preferentially eliminated cancer stem cells abrogating colony-forming unit activity and tumor initiation (24).…”
Section: Discussionmentioning
confidence: 99%
“…Antitumor activity of the hypoxiaactivated pro-drug (TH-302) was demonstrated in combination with bortezomib which improved survival of mice with myeloma (14). TH-302 also delayed onset and progression of acute myeloid leukemia (AML) xenograft model (23). Moreover, blocking HIF1a signaling, which is constitutively expressed in mouse lymphoma and human AML stem cells, preferentially eliminated cancer stem cells abrogating colony-forming unit activity and tumor initiation (24).…”
Section: Discussionmentioning
confidence: 99%
“…Since gluataminase inhibitors also cause mitochondrial apoptosis through an increase in glutamine level, an additional strategy to hinder mitochondrial oxidative phosphorylation might take advantage of the synergy between these drugs and ABT compounds [117]. Another intriguing possibility is to exploit hypoxia-activated prodrugs [81,118]. It has been demonstrated that after exposure to hypoxia and TH-302, a hypoxia-activated prodrug which under hypoxic conditions releases the DNA alkylating agent bromoisophohoramide mustard, chemoresistant AML cells became sensitive to cytarabine and undergo apoptosis; thus this represents the rational for phase I clinical trials in refractory AML [118].…”
Section: Potential Targetsmentioning
confidence: 99%
“…Another intriguing possibility is to exploit hypoxia-activated prodrugs [81,118]. It has been demonstrated that after exposure to hypoxia and TH-302, a hypoxia-activated prodrug which under hypoxic conditions releases the DNA alkylating agent bromoisophohoramide mustard, chemoresistant AML cells became sensitive to cytarabine and undergo apoptosis; thus this represents the rational for phase I clinical trials in refractory AML [118]. Leukemic cell-induced changes in stromal cell activities and the intrinsic alterations adopted by the BM microenvironment to promote AML development and progression might be additional treatment targets to hinder leukemic niches.…”
Section: Potential Targetsmentioning
confidence: 99%
“…TH-302 also effectively inhibited onset, progression of AML, and extended the overall survival, both in systemic AML xenograft models and mice with advanced AML disease. In vitro, TH-302 decreased HIF1a protein expression and reduced ROS production, which resulted in decreased proliferation, increased cellcycle arrest, and induced double-stranded DNA breaks (80). TH-302 is currently evaluated in phase I/II study in patients with relapsed/refractory multiple myeloma combination with dexamethasone, with or without bortezomib (NCT01522872).…”
Section: Targeting Hypoxic Cells With Prodrugsmentioning
confidence: 99%